Quality characteristics of thin-walled plastic injection parts - Noh, Shahril (2010)
The development of plastic injection product as consumer products, such as communication and electronic products have a tendency to be light, thin, short, and small. For example, a laptop computer product requires a smaller, variable and convenient style. Therefore, the shapes of laptop are changing and more features have to be tightly packed into smaller volume of the casing. In order to produce the casing, it must be thin-walled and also tough at a mean time. In plastic injection molding, the production of the thin-walled part is very difficult. It's hard, because melted plastic cannot easily fill the mold cavity. The most important problem in thin-walled parts is warpage. Therefore, this project was undertaken to study a thin-walled plastic product such as laptop lid casing, has quality characteristics during injection moulding process especially warpage and shrinkage. Software has been used to overcome this matter. The software can analysis and to predict quality of product after injection process. The software which be used were PRO/ENGINEER and Moldflow. PRO/E software is used for create model of product. Moldflow software is used for analysis and to predict result of quality product.This research used the classical experimental design with full factorial methods to determine the injection molding conditions, and the injection processes will simulate using the commercial software Moldflow. The product and mould design was designed by Pro/Engineer Software. Both molding conditions and factors were discussed regarding the degree of warpage of a thin shell part.